Pengaruh Perbandingan Ketan Putih (Oryza sativa glutinosa) Dan Ubi Jalar Ungu (Ipomoea Batatas L.) Terhadap Karakteristik Brem Cair - Bryan, Bryan; Duniaji, Agus Slamet; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i03.p19, 2021)
This study aimed to determine the effect of comparison between white glutinous rice and purple sweet potato on the chemical characteristic and sensory of brem beverage also the best ratio of white glutinous rice and purple sweet potato to produce brem beverage with the best characteristic. The design method used Completely Randomized Design with one treatment, namely the comparison of white glutinous rice and purple sweet potato (100:0%) (P0), 90%:10% (P1), 80%:20% (P2), 70%:30% (P3), 60%:40% (P4). This research repeats three times, resulting in 15 times experiments. The data obtained then analyzed with the Analysis of Variance, and if the treatments had a significant effect, continued with the Duncan Multiple Range Test. The best characteristics obtained from the comparison of white glutinous rice and purple sweet potato 80%:20% with the criteria reducing sugar value 8.57%, sugar value 28.86%, alcohol value 3.093%, pH 4.27, acid value 2.10%, antioxidant activity 32.63%, anthocyanin value 6.68 mg/L, mold/yeast value 5.67 x 101 log CFU/ml. The characteristic of the brem beverage color was violet and liked, the aroma was liked, the taste was sweet and liked, and overall acceptance was liked.